2017
DOI: 10.5539/sar.v6n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Challenges Facing the Small Farmers in the Green Scheme Projects in Namibia

Abstract: The paper uses a combination of theory and both quantitative and qualitative evidence to demonstrate the significance and challenges of agricultural development in Namibian green scheme projects. For quantitative, a structured questionnaire to produce descriptive statistics was administered to 135 small farmers while eight (8) project manager who were interviewed at the studied schemes as key informant served as source of qualitative information that pin pointed out challenges and opportunities, faced by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…On the other hand, livestock farming includes cattle, goats, sheep and pig production. According to Shapi (2017), the agricultural sector remains one of the key sectors in the Namibian economy as it has been the major provider of food, employment, income, and foreign exchange in the economy. The agricultural sector also supports other sectors such as transport and manufacturing among others, in providing the inputs for further processing of other products, thus, making it crucial to other sectors of the Namibian economy (Mubita, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, livestock farming includes cattle, goats, sheep and pig production. According to Shapi (2017), the agricultural sector remains one of the key sectors in the Namibian economy as it has been the major provider of food, employment, income, and foreign exchange in the economy. The agricultural sector also supports other sectors such as transport and manufacturing among others, in providing the inputs for further processing of other products, thus, making it crucial to other sectors of the Namibian economy (Mubita, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 1995, the Namibian government formulated the National Agriculture Policy (NAP) to guide agricultural development in the agricultural sector (Shapi, 2017). The policy aimed at increasing agricultural production, agro-processing, and marketing.…”
Section: Overview Of the Agricultural Sector In Namibiamentioning
confidence: 99%
See 1 more Smart Citation
“…The government normally buys small stock with the main purpose of supplying it to the beneficiaries of public programs to encourage their participation in livestock farming. Shapi (2017) reported that lack of access to effective and efficient markets is one of the factors that impede the sale of smallholder farmers' produce. Another marketing constraint were low prices offered at the market place.…”
Section: Marketing Constraints Faced By Small Stock Farmersmentioning
confidence: 99%
“…Literature also revealed that smallholder farmers face marketing constraints. Shapi (2017) reported the lack of effective markets as a constraint faced by smallholder farmers. Purchase of small stock at very low prices is another major concern (Bahta et al, 2013).…”
Section: Introductionmentioning
confidence: 99%